2022
DOI: 10.1111/jocn.16566
|View full text |Cite
|
Sign up to set email alerts
|

Ecological model of health behaviour of hypertensive stroke patients at the end of recovery period

Abstract: Aims andObjectives: This study aimed to construct a structural equation model guided by the ecological model to explore the factors influencing health behaviour among hypertensive stroke patients 6 months post-stroke. Background: Health behaviour is important for recurrence prevention in hypertensive stroke patients. Moreover, previous studies have indicated that health behaviour at the end of the recovery period is of particular concern. The ecological model provides an integrated perspective for explaining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Previous studies discovered that companionship was the best way to alleviate abnormal emotions ( 25 ). As for knowledge, researchers provided remote health guidance and disease prevention for the empty nesters to make them know more about chronic diseases and build their self-confidence in fighting with diseases, this is consistent with previous studies ( 26 ). Regarding COVID-19, previous studies have demonstrated that a large amount of COVID-19 information made people confused between true and false, which was the a cause of anxiety and depression ( 27 ).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies discovered that companionship was the best way to alleviate abnormal emotions ( 25 ). As for knowledge, researchers provided remote health guidance and disease prevention for the empty nesters to make them know more about chronic diseases and build their self-confidence in fighting with diseases, this is consistent with previous studies ( 26 ). Regarding COVID-19, previous studies have demonstrated that a large amount of COVID-19 information made people confused between true and false, which was the a cause of anxiety and depression ( 27 ).…”
Section: Discussionsupporting
confidence: 88%
“…The ecosystem theory model supports the idea that self-psychological adjustment is influenced by individual, family and social factors 28–30. Clinical characteristics, including clinical stage, Eastern Cooperative Oncology Group (ECOG) status 31.…”
Section: Introductionmentioning
confidence: 82%
“…The ecosystem theory model supports the idea that self-psychological adjustment is influenced by individual, family and social factors. [28][29][30] Clinical characteristics, including clinical stage, Eastern Cooperative Oncology Group (ECOG) status. 31 Demographic characteristics are important components of personal factors, such as age, gender and educational level.…”
Section: Open Accessmentioning
confidence: 99%
“…It can be divided into 5 layers: personal traits, behavior and/or lifestyle, interpersonal networks, socioeconomic status, and macro-environment. HEM has become widespread in the field of chronic disease research and the development of predictive models [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%